A Diagnosis of Maternal 22q Duplication and Mosaic Deletion following Prenatal Cell-Free DNA Screening - Melissa A. Hicks; Emilie Lalonde; Jessica Zoladz; Bernard Gonik; Salah Ebrahim (Case Reports in Genetics)
Concurrent microduplication and microdeletion of the chromosome 22q11.2 region are a rarely reported phenomenon. We describe a case of germline 22q11.21 microduplication syndrome with concurrent mosaic 22q11.2 deletion in a pregnant patient, identified by chromosomal microarray and FISH after noninvasive prenatal genetic screening (cfDNA) results discordant with family history. The patient was referred to maternal-fetal medicine (MFM) at 14 weeks’ gestation secondary to an SNP-based cfDNA result of a suspected maternal 22q11.2 deletion and a fetal risk of 1 in 2 for 22q11.2 deletion syndrome. The patient reported a similar cfDNA result in a previous pregnancy; however postnatal chromosomal microarray on that child identified an atypical 22q11.21 microduplication. We report the maternal chromosomal microarray findings of a germline 726 kb 22q11.21 duplication and a mosaic 1.33 Mb 22q11.2 deletion and highlight the copy number variant data generated by cfDNA in this unique case. This family adds to the limited literature of concurrent 22q11.2 microduplication and microdeletion carriers.